2016
DOI: 10.1007/s00603-016-0946-8
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Dynamic Tensile Failure of Rocks Subjected to Hydrostatic Confinement

Abstract: It is critical to understand the dynamic tensile failure of confined rocks in many rock engineering applications, such as underground blasting in mining projects. To simulate the in situ stress state of underground rocks, a modified split Hopkinson pressure bar system is utilized to load Brazilian disc (BD) samples hydrostatically, and then exert dynamic load to the sample by impacting the striker on the incident bar. The pulse shaper technique is used to generate a slowly rising stress wave to facilitate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In this study, we investigated the compression-induced tensile mechanical behaviors of the crystalline rock, combining the SHPB test and the GBM simulation. The experimental results showed that the macro tensile strength of the SJK granite depended on the loading rate, which was similar to findings obtained in previous studies [ 25 , 26 , 27 ]. However, previous studies rarely characterized the dynamic compression-induced tensile mechanical behaviors of the crystalline rock from the micromechanical viewpoint.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we investigated the compression-induced tensile mechanical behaviors of the crystalline rock, combining the SHPB test and the GBM simulation. The experimental results showed that the macro tensile strength of the SJK granite depended on the loading rate, which was similar to findings obtained in previous studies [ 25 , 26 , 27 ]. However, previous studies rarely characterized the dynamic compression-induced tensile mechanical behaviors of the crystalline rock from the micromechanical viewpoint.…”
Section: Discussionsupporting
confidence: 90%
“…Out of the quasi-static case, the Brazilian test was extended to the dynamic case by making full use of the split Hopkinson pressure bar (SHPB) system [ 25 , 26 , 27 ]. Besides the internal heterogeneous microstructure, the loading rate significantly influenced the tensile behaviors of the rock materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai and Xia [13] conducted dynamic Brazilian disc tests on Barre granite and confirmed the dependence between the tensile strength and loading rate. Wu et al [14] carried out the dynamic tensile tests of rock under the hydrostatic confinement.…”
Section: Introductionmentioning
confidence: 99%
“…Natural rock has a high degree of variability, making it difficult to generate consistent results from tests that need a number of different samples even if they are taken from the same rock body. In addition, rocks normally being brittle materials, specimens are usually destroyed in most mechanical tests (Wu et al 2016), meaning that repeat tests or investigation of other properties cannot be carried out.…”
Section: Uses and Limitations Of Natural Rock Samplesmentioning
confidence: 99%